2004
DOI: 10.3106/mammalstudy.29.55
|View full text |Cite
|
Sign up to set email alerts
|

Importance of walleye pollock (Theragra chalcogramma) to wintering ribbon seals (Phoca fasciata) in Nemuro Strait, Hokkaido Japan

Abstract: Abstract. Many ribbon seals (Phoca fasciata) appear in winter in Nemuro Strait, eastern Hokkaido. We propose that their presence is partly related to an exploitation of the large numbers of spawning walleye pollock (Theragra chalcogramma). To investigate feeding habits of ribbon seals in winter, we sampled stomachs from seals for prey composition and size taken in the strait from FebruaryApril 1996-1998. Nine fish and five squid species were identified from sixty-four seal stomachs. Walleye pollock and magistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Since ribbon seals were present far from known breeding grounds and well outside of the breeding season, we surmise that they were either feeding in the vicinity of the recorder or moving to or from northern foraging areas. Studies of stomach contents suggest that ribbon seals feed primarily in the midwater, often at the edge of the continental slope (Deguchi et al, 2004), which fits with the depth profile of the recording site. Although little is known about feeding behavior of ribbon seals from July through March, a number of studies have shown that Arctic cod (Boreogadus saida) is at least an occasional prey species (e.g., Shustov, 1965;Frost and Lowry, 1980;Dehn et al, 2007).…”
Section: Seasonal Presence and Variation In Acoustic Repertoirementioning
confidence: 82%
See 1 more Smart Citation
“…Since ribbon seals were present far from known breeding grounds and well outside of the breeding season, we surmise that they were either feeding in the vicinity of the recorder or moving to or from northern foraging areas. Studies of stomach contents suggest that ribbon seals feed primarily in the midwater, often at the edge of the continental slope (Deguchi et al, 2004), which fits with the depth profile of the recording site. Although little is known about feeding behavior of ribbon seals from July through March, a number of studies have shown that Arctic cod (Boreogadus saida) is at least an occasional prey species (e.g., Shustov, 1965;Frost and Lowry, 1980;Dehn et al, 2007).…”
Section: Seasonal Presence and Variation In Acoustic Repertoirementioning
confidence: 82%
“…Ribbon seals are well adapted to deep diving (Burns et al, 1981b). Studies of stomach contents indicate that ribbon seals may feed in deeper water (> 300 m) than either ringed seals or bearded seals, and that they prefer to forage near the bottom on the continental slope (Deguchi et al, 2004).…”
Section: Ribbon Sealsmentioning
confidence: 99%
“…jj Data sources: belugas (Seaman et al 1982, Heide-Jørgensen andTeilmann 1994), narwhals (Laidre and Heide-Jørgensen 2005a), bowheads (Lowry 1993, ringed seals (Lowry et al 1980a, Lydersen 1998, Siegstad et al 1998, Wathne et al 2000, bearded seals (Lowry et al 1980b, Antonelis et al 1994, walrus (Fay 1982, Gjertz and Wiig 1992, polar bears (Smith 1985, Calvert and Stirling 1990, Smith and Sjare 1990, Stirling and Øritsland 1995, subarctic seals (Bukhtiyarov et al 1984, Burkanov 1989, Frost and Lowry 1990b, Lydersen et al 1991, Murie and Lavigne 1991, Sergeant 1991, Beck et al 1993, Lowry et al 1998, Folkow and Blix 1999, Deguchi et al 2004, Hammill et al 2005.…”
Section: Species Rankings and Index Resultsmentioning
confidence: 99%
“…In the Okhotsk Sea, juveniles feed on euphausiids and shrimp, whereas adults feed on mostly pollock (Fedoseev 2002). However, when not over the continental shelf ribbon seals may feed in deeper waters and dive to deeper depths (Deguchi et al 2004).…”
Section: Subarctic Ice-associated Sealsmentioning
confidence: 99%
“…Lampanyctus jordani is widely distributed in the subarctic North Pacific Ocean 3 and is one of the most dominant myctophids in the western part of the ocean 4 . Lampanyctus jordani has been reported to be preyed upon by marine mammals such as ribbon seal Phoca fasciata 5 and Dall's porpoise Phocoenoides dalli 6 . Further, over the continental slope in the Tohoku area, dominant demersal fishes such as Pacific cod Gadus macrocephalus , walleye pollock Theragra chalcogramma and threadfin hakeling Laemonema longipes consume L. jordani 7 .…”
Section: Introductionmentioning
confidence: 99%